2022
DOI: 10.3390/app12094608
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Dynamic Splitting Mechanical Properties of Annular Sandstone Specimens with Temperature–Water Coupling in a Coal Mine

Abstract: With the gradual deepening of mine excavation depth, the strong disturbance of deep strata becomes more and more obvious. Rock’s failure under blasting mainly depends on its dynamic tensile strength. The changes in rock’s dynamic properties are obviously affected by temperature and water. In order to study the dynamic tensile properties of annular sandstone specimens under the influence of temperature and water, deep sandstone was drilled, followed by water bath tests at eight temperatures (25~95°C). It can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…It first decreased, and then increased with the increase in the ice-filled crack angle. The dynamic tensile properties of annular sandstone specimens under the influence of temperature and water were studied by Ping et al [6]. The variation in the mass, volume growth rates, density growth rate, dynamic compressive strength, average strain rate, and peak strain with water temperature was evaluated.…”
Section: Failure Behavior and Mechanical Characteristics Of Rock Mass...mentioning
confidence: 99%
“…It first decreased, and then increased with the increase in the ice-filled crack angle. The dynamic tensile properties of annular sandstone specimens under the influence of temperature and water were studied by Ping et al [6]. The variation in the mass, volume growth rates, density growth rate, dynamic compressive strength, average strain rate, and peak strain with water temperature was evaluated.…”
Section: Failure Behavior and Mechanical Characteristics Of Rock Mass...mentioning
confidence: 99%
“…Furthermore, a functional relationship was established between water temperature and the peak strain observed. The utilization of XRD and SEM tests provided conclusive evidence demonstrating that alterations in water temperature have the ability to modify the internal structure of sandstone, consequently affecting its dynamic properties 38 . Zhang tested various impact speeds on sandstone, and the findings suggested that the impact velocity had a major influence on the rock's mechanical characteristics, in addition to proposing some new mechanical coefficients 39 .…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, to prevent the occurrence of disasters and ensure the safe operation of underground space projects, it is necessary to carry out experimental research on the dynamic mechanics of temperature-water-coupled sandstone under dynamic and static combined loading. The sandstone used in this paper was obtained from the roadway of the Pan Er Coal Mine in Huainan City, Anhui Province, China, based on previous kinetic tests of local sandstone by Ping et al It was found that the kinetic properties of sandstone change at 45 • C and that the strength of sandstone is weakest at 45 • C [31]. The dynamic and static combined SHPB device was used to carry out impact compression tests on sandstone with temperature-water-coupled effects at 45 • C under eight types of axial pressure (0.5~4.0 MPa) loading and without axial pressure loading.…”
Section: Introductionmentioning
confidence: 99%